2018
DOI: 10.4236/jwarp.2018.109050
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Level Prediction Using Artificial Neural Networks: A Case Study in Tra Noc Industrial Zone, Can Tho City, Vietnam

Abstract: The objective of this study is to predict groundwater levels (GWLs) under different impact factors using Artificial Neural Network (ANN) for a case study in Tra Noc Industrial Zone, Can Tho City, Vietnam. This can be achieved by evaluating the current state of groundwater resources (GWR) exploitation, use and dynamics; setting-up, calibrating and validating the ANN; and then predicting GWLs at different lead times. The results show that GWLs in the study area have been found to reduce rapidly from 2000 to 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This may be the result of groundwater exploitation being gradually phased-out due to the expansion of the water supply network from surface water. In addition, due to lack of data on GWR exploitation for the whole city, based on the assessment of the exploitation rate of GWR in Tra Noc Industrial Zone carried out by Ty et al (2018) [22], a total exploitation rate of GWR from 2004 to 2016 is shown in Figure 4. The [30].…”
Section: Fluctuation Of Gwr In Can Tho Citymentioning
confidence: 99%
See 1 more Smart Citation
“…This may be the result of groundwater exploitation being gradually phased-out due to the expansion of the water supply network from surface water. In addition, due to lack of data on GWR exploitation for the whole city, based on the assessment of the exploitation rate of GWR in Tra Noc Industrial Zone carried out by Ty et al (2018) [22], a total exploitation rate of GWR from 2004 to 2016 is shown in Figure 4. The [30].…”
Section: Fluctuation Of Gwr In Can Tho Citymentioning
confidence: 99%
“…It was found that the trend of this dropdown in deep wells was highly associated with extraction rates. In addition, Ty et al (2018) conducted research in the Tra Noc Industrial Zone of Can Tho city to assess the current status of exploitation, GWLs changes and management of GWR, from which a relationship between groundwater extraction, the water level in the Hau River (CTH-039803 station) and GWLs at monitoring stations/wells was established [21,22]. The results showed that the extraction of groundwater in the Tra Noc Industrial Zone led to an over-exploitation of GWR.…”
Section: Introductionmentioning
confidence: 99%